Quality Evaluation of Fast-Growing Wood Impregnated with Nano-Silica Synthesized from Betung Bamboo Stems - Rahayu, Istie; Khoerudin, Riki; Wahyuningtyas, Irma; Prihatini, Esti; Ismail, Rohmat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Sengon (Paraserianthes falcataria L. Nielsen.) and jabon (Anthocephalus cadamba Miq.) are fast-growing wood of low quality. This study aims to overcome the disadvantages of low-quality wood via impregnation using monoethylene glycol (MEG), and nano-silica synthesized from betung bamboo stems (Dendrocalamus asper). Nano-silica was obtained by the ultrasonication method, with the average size and zeta potential at 93 nm and -44.21 mV, respectively. This study used five different solutions: untreated, 50% MEG, MEG-Silica 0.5%, MEG-Silica 0.75%, and MEG-Silica 1%. The impregnation process began when a vacuum of 0.5 bar was applied for 60 minutes and continued with a pressure of 2.5 bar for 120 minutes. The results showed that sengon and jabon experienced an increase in quality as seen from the parameters of weight percent gain, specific gravity, modulus of elasticity, modulus of rupture, hardness, color brightness, and durability against dry wood and subterranean termites. Besides, the strength and durability classes of both kinds of wood also improved to III and IV, respectively, with the solution’s concentration gradually increasing. Based on the results, MEG-Silica 1% is the most influential solution in improving the physical-mechanical properties and durability of sengon and jabon wood. Keywords: Anthocephalus cadamba, Dendrocalamus asper, impregnation, nano-silica, Paraserianthes falcataria